Słowniki w słownikach – rozważania leksykograficzne: dykcjonarz i wokabularz - Migdał, Jolanta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The article is a continuation of research addressing the issue of the dictionary history of names of lexicographic collections. The considerations concern two lexemes: dykcjonarz and wokabularz. The analyses are presented against the background of the history of the most popular contemporary term: słownik (‘dictionary’). Both lexemes presented in the article are older than słownik. The name dykcjonarz has been used in Polish since the 16th century, while wokabularz is attested from the beginning of the 17th century. Both lexemes come from Latin, but dykcjonarz came into Polish through the mediation of French. The authors of a specialist publication on lexicography refer both entries to the old Polish lexicography of the period from the 16th to the 18th century. General dictionaries usually treat both names as words with a chronological meaning: old, obsolete, archaic or historical. The lexicographic history of both words shows the stability of their meaning. Exceptionally, dictionaries mark the nuances of meaning of the entry dykcjonarz and indicate additional meanings of wokabularz, both of which, however, belong to old or specialist lexis.